Assessing the Role of Capital Structure, Investment Policy, Profitability, and Growth in Determining Firm Value in Technology Companies Listed on the Indonesia Stock Exchange in 2020-2022 - Ni Made Candra Manikasari; I Gde Ary Wirajaya (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Corporate valuation embodies the market's perception of an enterprise’s performance and prospective trajectory, serving as a critical barometer of its financial health, competitive standing, and long-term sustainability. This investigation seeks to elucidate the extent to which determinants such as capital configuration, investment paradigm, profitability metrics, and expansion dynamics influence corporate worth. The inquiry concentrated on technology enterprises listed on the Indonesia Stock Exchange during the period 2020–2022. The sample was delineated via purposive sampling, culminating in 57 discrete observations. Analytical procedures were executed employing multiple linear regression within the SPSS environment. Empirical results revealed that capital architecture, investment disposition, profitability, and growth trajectories all exert a salutary effect on firm valuation. This study augments comprehension of signaling theory, the trade-off paradigm, and the mechanisms through which these variables modulate corporate value. These results offer valuable guidance for managers seeking to maximize shareholder wealth and for investors in assessing the potential of technology sector enterprises.